PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA, DAN KESIAPAN UNTUK BERUBAH TERHADAP KINERJA KARYAWAN COLLECTION PT. BANK BTN KC SOLO DI MASA PANDEMI COVID-19 - Negoro, Guntur Adi; Rachmawati K., Ida Ayu Kade (Jurnal Kelola: Jurnal Ilmu Sosial, 2023)
The purpose of this research is to learn how PT. Bank BTN KC SoIo's Collection unit personnel respond to a leader's transformational style of management, as well as how open they are to change. For this quantitative study, 20 valid samples were obtained using random sampling, and their responses were used to compile the data. Based on the data presented here, the authors draw the following conclusions about the relationship between transformational leadership and employee performance: it has a negative effect, the work environment has a positive effect, and readiness to change does not significantly affect employee performance.